AR-KIO: Augmented Reality-based Application as Instructional Media on Input and Output Device Component. - Rohmah, Nur Hidayattur; Sujana, Yudianto; Yuana, Rosihan Ari (IJIE (Indonesian Journal of Informatics Education), 2017)
The rapid technology development can be utilized in various fields, especially in education. For example, is augmented reality-based learning media. The learning media can be applied to all the subject matter, including the subject of input and output component devices. Based on the observations that already made, there are some problems such as there is no interactive learning media and limited props in the laboratory. Though the subject of input and output component devices require three-dimensional visualization, especially input output components that are difficult to find in the school environment. The purpose of this study is to determine the feasibility of instructional media applications that have been developed. The research method used is research development method. The tests conducted by media experts, content experts, users and smartphone devices with different specifications. Media expert testing using instruments that refer to aspects of the functionality of ISO 9126 with the percentage acquisition of 100%. Content expert testing using the instrument that refers aspects of learning design with the acquisition percentage of 88%. Meanwhile, user testing uses an instrument that refers to the usability aspect of ISO 9126 with a percentage gain of 83.4%. In addition, there are testing the software with android smartphone platform that has different specifications. The advantages of this application can run on a smartphone with minimum 512 MB RAM specs, Android OS Jelly Bean 4.3 and qHD screen resolution.